2017
DOI: 10.1152/ajpendo.00269.2016
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic hyperglycemic effects of vasopressin in normal rats: involvement of V1A receptors

Abstract: Recent epidemiological studies have revealed novel relationships between low water intake or high vasopressin (AVP) and the risk of hyperglycemia and diabetes. AVP V and V receptors (R) are expressed in the liver and pancreatic islets, respectively. The present study was designed to determine the impact of different levels of circulating AVP on glucose homeostasis in normal Sprague-Dawley rats, as well as the respective roles of VR and VR. We showed that acute injection of AVP induces a dose-dependent increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 58 publications
5
31
0
Order By: Relevance
“…VP stimulates glucagon secretion by activation of V1bR in α-cells of pancreatic islets [3] which is concordant with our finding that fasting glucagon concentration was reduced upon water-induced suppression of VP (copeptin). In addition, we recently showed in rodents that during conditions of high VP, selective pharmacological blockade of V1bR with SR149415 resulted in reduction of plasma glucagon [40]. Taken together, our finding that water-induced decrease of copeptin in water-responders is associated with fasting glucagon reduction encourages longterm studies of anti-diabetic effects of water supplementation in subjects with low water intake.…”
Section: Discussionsupporting
confidence: 63%
“…VP stimulates glucagon secretion by activation of V1bR in α-cells of pancreatic islets [3] which is concordant with our finding that fasting glucagon concentration was reduced upon water-induced suppression of VP (copeptin). In addition, we recently showed in rodents that during conditions of high VP, selective pharmacological blockade of V1bR with SR149415 resulted in reduction of plasma glucagon [40]. Taken together, our finding that water-induced decrease of copeptin in water-responders is associated with fasting glucagon reduction encourages longterm studies of anti-diabetic effects of water supplementation in subjects with low water intake.…”
Section: Discussionsupporting
confidence: 63%
“…They also found that specific variants of the AVP gene were also associated with increased risk for hyperglycemia, and that men expressing these variants also had higher plasma copeptin (no association was found in women, who, on average, tend to have lower plasma copeptin than men). This finding is consistent with previous preclinical evidence that AVP contributes to metabolic dysfunction via V1a and V1b receptors expressed in hepatocytes and pancreatic islets, respectively [47][48][49][50].…”
Section: New Statistical Approaches Help To Establish a Probable Caussupporting
confidence: 93%
“…V1bR SSR149415 antagonist did not change the hyperglycaemic response to acute injection AVP, and V1bR agonist d(Leu4, Lys8)VP had no effect on glycaemia. Thus, these results support a major role of V1aR in the humoral control of glycaemia .…”
Section: Overview Of Short‐term Effects Of Avp On Glucose Metabolism supporting
confidence: 75%
“…However, whilst V1bR antagonist pretreatment did not change the basal insulinaemia or the insulin response to hyperglycaemia induced by AVP, it enhanced the fall in glucagon secretion after AVP injection . This suggests that endogenous AVP constantly stimulates the glucagon secretion and thus participates in the physiological regulation of glucagon secretion in normal rats.…”
Section: Overview Of Short‐term Effects Of Avp On Glucose Metabolism mentioning
confidence: 88%
See 1 more Smart Citation